IAU Office of Astronomy for Development: Task Force Children and School Education. (5th March 2015) - Russo, Pedro; Gomez, Edward
Abstract: The main mission of the IAU OAD Task Force on Children and School Education is to support the implementation of the pre-tertiary education part of the IAU Strategic Plan 'Astronomy for Development'. In this presentation we will give an overview of the role and programme of the task force as well as a general discussion about the past, present and future IAU education activities and programmes.